PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP LEVEL TRANSPARANSI GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN MANUFAKTUR DI BEI - Widaryanti .; Luhgiatno . (STIE Pelita Nusantara Semarang, 2016)
This study aims to investigate the characteristics of companies that affect the level of transparency of corporate governance on manufacturing companies listed in Indonesia Stock Exchange. The factors used were firm characteristics (firm size, listing status, the status of the auditor, the type of industry, the level of dispersed ownership) to investigate its effect on the level of transparency of corporate governance (GCG). Population in this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2014 which amounted to 141. Samples obtained a number of 137. The study states that the size of the company significantly affect the level of transparency GCG. It is based on a significance level of t- calculated that 0,005 smaller than 0.05, whereas the t value obtained was 2.878 greater than t-table value that is equal to 1,660. Status auditor does not significantly affect the level of transparency of GCG. It is based on a significance level of t-count amounted to 0.322 greater than 0.05, whereas the t value obtained was 0.994, which is smaller than t-table value that is equal to 1,660. Type of industry do not significantly affect the level of transparency of GCG. It is based on a significance level of t-count amounted to 0.770 greater than 0.05, whereas the t value obtained was 0.294, which is smaller than t-table value that is equal to 1,660. Level dispersed ownership affect the level of transparency of GCG. This is based on the value of significance (Sig.) of 0.000 which is smaller than 0.05, whereas the t value obtained was 3.604, which is larger than t-table value that is equal to 1,660. The size of the Company, Auditor Status, Type Industrial and Ownership Level dispersed simultaneously significant effect on Transparency Level GCG with F calculate equal to 5.108 and the value of significance (Sig.) of 0.001.